Southern Ocean influence on the eastern tropical North Pacific's intermediate‐depth circulation during the Last Glacial Maximum. (28th August 2015) - Carriquiry, José D.; Sanchez, Alberto; Leduc, Guillaume
Abstract: The oxygen and carbon isotopic compositions of benthic foraminiferal tests were measured on sedimentary sequences retrieved on the Magdalena Margin, off southern Baja California, Mexico. We reconstruct the hydrographic changes along the water column that occurred in the northeastern tropical Pacific since the Last Glacial Maximum (LGM) and compare those changes to the ones that occurred in the northwest Pacific (NWP, i.e., off Japan and Russia), in the northeast Pacific along the Californian Margin, as well as in the southeast Pacific (off Chile). The foraminiferal δ 18 O depth profiles across the North and southeast Pacific show similar trends between the LGM and the Holocene, indicating that changes in the oceanographic conditions between 400 and 2000 m depth were very similar. Changes in the isotopic composition of dissolved inorganic carbon ( δ 13 CDIC ) in the Baja California Margin since the Last Glacial Maximum were reconstructed using the δ 13 C of shallow endobenthic foraminifers U . peregrina and the epibenthic Cibicides mckannai . The most striking result is a marked shift toward more positive δ 13 C values below 1200 m depth in the northeast Pacific (NEP) during the Holocene (relative to the LGM). This observation suggests that a nutrient‐rich water mass ventilated the NEP during the LGM. At a basin scale, the δ 13 C values of NEP waters at intermediate depths were more negative relative to the NWP and southeast Pacific during the LGM, suggesting that the nutrient‐rich water column along the NEP (i.e., Baja California Margin) was confined in that area as observed today. Key Points: δ 13 C data refine glacial Pacific water mass geometry at intermediate depth California Margin was the terminus of LGM circulation Comparison of δ 13 C profiles suggests greater contribution of Antarctic waters